Birds as Suppliers of Seed Dispersal in Temperate Ecosystems: Conservation Guidelines from Real‐World Landscapes - Garcia, Daniel (2010)
Seed dispersal by animals is considered a pivotal ecosystem function, driving plant community dynamics in natural habitats as well as vegetation recovery in human-altered landscapes. However, there is a lack of suitable ecological knowledge to develop basic conservation and management guidelines for this ecosystem service. Essential questions, such as how far the abundance of frugivorous animals predicts seeding function in different ecosystems, and how anthropogenic landscape heterogeneity conditions the role of dispersers, remain poorly answered. In three temperate ecosystems, we studied seed dispersal by frugivorous birds in landscape mosaics shaped by human disturbance. By applying a standardized design across systems, we related the frequency of occurrence of bird-dispersed seeds throughout the landscape to the abundance of birds, the features of habitat and the abundance of fleshy fruits. The abundance of frugivorous birds in itself predicted partially the occurrence of dispersed seeds through the entire landscape of all ecosystems studied. Even those landscape patches impoverished due to anthropogenic degradation maintained the seed dispersal function when visited intensively by birds. Nonetheless, human-caused landscape heterogeneity largely conditioned seed deposition, by modifying the availability of woody vegetation and/or fruit resources that attracted birds and hence promoted seed dispersal. The relative role of woody cover and fruit availability on seed dispersal differed among systems. We suggest that the strategies to manage seed dispersal for ecosystem preservation or restoration should consider that: (i) the abundance of frugivorous birds may be a surrogate of landscape-scale seed dispersal in temperate ecosystems, and an indicator of  patch quality for the seeding function; (ii) woody cover and fruit resource availability are key landscape features driving seedfall patterns; and (iii) birds act as mobile links that connect landscape patches of different degrees of degradation and/or habitat quality via seed deposition.